Mechanochemical preparation of red clover extract/β-cyclodextrin dispersion: Enhanced water solubility and activities in alleviating high-fat diet-induced lipid accumulation and gut microbiota dysbiosis in mice. (15th September 2023) - Guo, Zili; Liu, Yilin; Xiang, Jiani; Liang, Xianrui
Graphical abstract: Highlights: The RC/ β -CD dispersion was prepared to improve its solubility. RC/ β -CD dispersion showed better effects on alleviating lipid accumulation. RC/ β -CD dispersion could regulate gut microbiota dysbiosis. The RC/ β -CD dispersion could increase the acetic and butyric acid in the gut. Abstract: Red clover (RC) extract is rich in isoflavones (formononetin and biochanin A) that have various biological functions. However, its low water solubility limits its bioavailability. In this study, an RC extract/ β -cyclodextrin (RC/ β -CD) dispersion was prepared by ball milling to enhance its water solubility and biological availability. The water solubility of formononetin and biochanin A was 34.45 and 13.65 μg/mL (increased to 3.11 and 2.14 times higher than that of RC alone), respectively. The alleviating effects of the dispersion on lipid accumulation and gut microbiota were evaluated in mice. The RC/ β -CD dispersion showed a better effect on inhibiting lipid accumulation, especially on total triglycerides. The dispersion group had a higher relative abundance of Akkermansia, Muribaculaceae, and Bacteroides than RC alone, along with a higher level of acetic and butyric acid. The study provides a feasible way for improving the bioaccessibility and bioactivity of RC isoflavones in red clover.